FAKTOR-FAKTOR PASCA PANEN YANG MEMENGARUHI MUTU KAKAO - Endang, Sri; Jumiono, Aji (Jurnal Ilmiah Pangan Halal, 2020)
The cocoa industry has enormous potential to be used as a driver for economic growth and distribution of income from farmers and the government. The post-harvest process of cocoa pods greatly affects the final quality of the cocoa beans produced. The post-harvest stages of cocoa pods include fruit splitting and sorting, fermentation of cocoa, soaking and washing, drying and tempering, as well as the warehousing process. Post-harvest processing of cocoa plants to improve the quality of the cocoa harvest owned by farmers. Fermented beans will improve the taste and quality of the cocoa beans, when the cocoa beans are processed it will produce good cocoa. Cocoa beans that go through a good post-harvest processing process will be stored longer without reducing their quality and can meet the quality standards of cocoa beans according to SNI 2323: 2008 which has been implemented since 2011. Keywords: Cocoa beans, Quality, Post-harvest process